Semiconductor Photocatalysis Materials, Mechanisms and Applications - Cao, Wenbin (IntechOpen, 2016)
Photocatalysis is a hot topic because it is an environmentally friendly approach toward the conversion of light energy into chemical energy at mild reaction environments. Also, it is well applied in several major areas such as water splitting, bacterial inactivation, and pollutants elimination, which is a possible solution to energy shortage and environmental issues. The fundamental knowledge and the frontier research progress in typical photocatalytic materials, such as TiO2-based and non-TiO2-based photocatalysts, are included in this book. Methods to improve the photocatalytic efficiency and to provide a hint for the rational design of the new photocatalysts are covered.